Efficient conversion of NO with CeO2/TiO2 using non-thermal plasma. Issue 6 (February 2019) - Adwek, George; Shen, Boxiong; Yang, Jiancheng; Siagi, Zachary; Wang, Jianqiao; Cicilia, Kemunto M.; Arowo, Moses; Julius, Gane; Kang, Dongrui
Abstract: Alternating current (AC) dielectric barrier discharge induced non-thermal plasma (NTP) has been used to experimentally investigate conversion of Nitrogen Oxide (NO) over CeO2 /TiO2 catalyst. The role of heterogeneous catalyst (TiO2 /CeO2 ) has also been investigated, NO conversion has been examined in terms of various operating parameters including temperature, voltage, flue gas flow rate, specific energy density, water vapour content and oxygen content. The conversion mechanism of NO was distinctly discussed. To understand the effects of NTP on CeO2 /TiO2 catalyst properties and the influence of CeO2 /TiO2 catalyst on NTP, SEM, BET, XRD, TPR were carried out. SEM reveals that increase in temperature during NTP catalytic reactions affect the morphology of the catalyst hence decreasing NO oxidation efficiency, the results also show that surface area and pore properties of the catalyst plays a significant role in plasma catalytic reaction. The maximum NO oxidation conversion efficiency attained was 93% at SED of 91JL −1 .